The relationship between physical performance and quality of life and the level of physical activity among the elderly - Lekshmi Prasad; Jean Fredrick; R Aruna (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Loss of physical function during the process of aging might affect the quality of life. Physical function assessment tests predicts outcomes such as falls, institutionalization, and death. Studies assessing the association of physical function with quality of life and physical activity level of elderly population in India is scarce. Hence we aimed to assess the physical function of community dwelling older adults and to determine its association with physical activity levels and quality of life. MATERIALS AND METHODS: This was a cross-sectional analytical study. 89 community dwelling older adults between 60 and 80 years of age were recruited. Physical function was assessed by standing balance, walking speed, and grip strength. Quality of life was assessed by WHO QOL BREF questionnaire and physical activity level was assessed by International Physical activity Questionnaire. RESULTS: Standing balance was reduced in 24% and walking speed was decreased in 33% of the participants. Males had higher walking speed, and grip strength. Quality of life was better among males. Standing balance, walking speed and grip strength was significantly higher in moderate - heavy activity levels. There was positive correlation between physical function and quality of life. There was also positive correlation between physical activity level and quality of life. CONCLUSION: Physical function, quality of life and physical activity level were decreased. Males had better physical function and quality of life. Physically active individuals had better physical function and quality of life. Early detection of decreased physical function and increase in physical activity level could result in better quality of life among elderly.